(untitled) - 1986-; 1986-; Snow, Brittany; 1973-; Marsden, James; Efron, Zac; Kelley, Elijah; Janney, Allison; ODonnell, Mark.; Waters, John; 1946-; 1943-; et al. (Burbank, CA, 2007)
In 1962 Baltimore there are changes in the air. Plus-sized teen Tracy Turnblad, with big hair and even bigger heart, has only one passion, to dance. She wins a spot on the local TV dance program, "The Corney Collins Show" and is transformed overnight from outsider to irrepressible teen celebrity. The trendsetting Tracy aims to win the heart of teen-dream Link Larkin and stand up for what she believes in.
Keywords: Drama; Drama; Teen television programs; United States; Drama; United States; United States; Overweight persons; Drama; Conduct of life; High school students; Mass media and race relations; Comedy films; Video recordings for the hearing impaired; Feature films; Dance drama; Musical films